2014
DOI: 10.1530/joe-14-0164
|View full text |Cite
|
Sign up to set email alerts
|

Automated image analysis of a glomerular injury marker desmin in spontaneously diabetic Torii rats treated with losartan

Abstract: Diabetic nephropathy is a major complication in diabetes and a leading cause of end-stage renal failure. Glomerular podocytes are functionally and structurally injured early in diabetic nephropathy. A non-obese type 2 diabetes model, the spontaneously diabetic Torii (SDT) rat, is of increasing preclinical interest because of its pathophysiological similarities to human type 2 diabetic complications including diabetic nephropathy. However, podocyte injury in SDT rat glomeruli and the effect of angiotensin II re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
(38 reference statements)
0
34
0
Order By: Relevance
“…Conversely, in the control group, FPE demonstrated no significant changes until 25 weeks. Furthermore, we evalu- ated the expression of desmin, a known marker of podocyte injury [18,19], whose increased expression during podocyte injury was shown in a model leading to FSGS [18]. In this study, desmin showed increased expression compared with the control group from 2 weeks on CsA treatment (p < 0.05; Fig.…”
Section: Timing Relationship Between Pec Activation and Podocyte Injurymentioning
confidence: 65%
“…Conversely, in the control group, FPE demonstrated no significant changes until 25 weeks. Furthermore, we evalu- ated the expression of desmin, a known marker of podocyte injury [18,19], whose increased expression during podocyte injury was shown in a model leading to FSGS [18]. In this study, desmin showed increased expression compared with the control group from 2 weeks on CsA treatment (p < 0.05; Fig.…”
Section: Timing Relationship Between Pec Activation and Podocyte Injurymentioning
confidence: 65%
“…There is evidence that desmin also connects the sarcomere to the ECM through desmosomes which is likely important in signaling between the ECM and the sarcomere in regulating tissue contraction and movement [41]. Of note, prior studies suggest that desmin is a sensitive marker of podocyte injury [43]. Also, desmin mRNA and protein are increased in cultured mouse podocytes and in vivo study it has been reported that desmin is increased in damaged mouse podocytes by insults of numerous kidney disorders, suggesting that desmin is involved in podocyte injury [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that desmin also connects the sarcomere to the ECM through desmosomes which is likely important in signaling between the ECM and the sarcomere in regulating tissue contraction and movement [32]. Of note, prior studies suggest that desmin is a sensitive marker of podocyte injury [34]. Also, desmin mRNA and protein are increased in cultured mouse podocytes and in vivo study it has been reported that desmin is increased in damaged mouse podocytes by insults of numerous kidney disorders, suggesting that desmin is involved in podocyte injury [35, 36].…”
Section: Discussionmentioning
confidence: 99%